Kinetics of biolubricant synthesis from jatropha curcas oil using Paphia undulata as a solid catalyst - Fatimah Azzahra’, Misebah (2017)
Nowadays, there is growing concern in looking for a renewable source of lubricant due to increasing demand for industrial applications besides depletion of world petroleum resource with uncertainty in petroleum supply has stimulated the search for biolubricants as an environmental friendly alternative source. Therefore, the research has been done using Jatropha curcas oil for biolubricant as new source over derived calcium oxide from Papia undulata shell as a solid catalyst. In addition, the research aims to determine the kinetic reaction for transesterification of Jatropha curcas oil on biolubricant yield. The first step in the research method was esterification process of free fatty acid (FFA) in Jatropha curcas oil, for reduction of the free fatty acid value and production of Jatropha curcas oil metyl ester (JCOME). This was followed by the synthesis of lubricant from blending JCOME with TMP by evaluating the process conditions. The final products were analyzed using gas chromatography mass spectorophotometer (GCMS) for JCOME production and gas chromatography with Flame Ionization Detector (GC-FID) for Jatropha biolubricant production. The optimum reaction for JCOME production was found to be at methanol/oil ratio of 6:1, catalyst amount of 4 wt.%, temperature of 60 oC and reaction time of 3 hours with the highest yield being 93.33%. Meanwhile Jatropha biolubricant optimum conditions were at 110 0C, 3 h, 4:1 of JME: TMP and 3% w/w of catalyst with 96.66% of TMP conversion and 78.67% of TE composition. The reaction was determined to fit the second order kinetics model with overall rate constant of 0.0427 (%w/w min °C)-1 and activation energy of 2.2 kJ/mol.